O , X , Y , Z are four points on a 3D Cartesian space, where O is the origin, X a point on the x -axis, Y a point on the y -axis, and Z a point on the z -axis.
Now, the area of △ O X Y is given by a , the area of △ O Y Z by b , and the area of △ O X Z by c .
Find the area of △ X Y Z in terms of a , b , c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's tough
For this question, we could start by find some calculation techniques for triangle's area.
And substitute the area of three triangle a , b , and c in.
Here, I choose Heron's formula.
Which is
a r e a = s ( s − A ) ( s − B ) ( s − C )
s = 2 ( A + B + C )
Where A , B , and C is three side of the triangle.
By Pythagoras Theorem, we could find three side of the triangle as:
A = x 2 + y 2
B = y 2 + z 2
C = z 2 + x 2
As we could see, area a , b , and c could be express as
a = 2 x ⋅ y
b = 2 y ⋅ z
c = 2 x ⋅ z
Since we would like to take x , y , and z out from the function.
We could see that:
( y ⋅ z ) ( x ⋅ y ) ( x ⋅ z ) = x 2
So if we apply this to a, b, and c, we could pull x 2 , y 2 , and z 2 out.
2 b a ⋅ c = 2 ( 2 y ⋅ z ) ( 2 x ⋅ y ) ( 2 x ⋅ z ) = x 2
2 c a ⋅ b = 2 ( 2 x ⋅ z ) ( 2 x ⋅ y ) ( 2 y ⋅ z ) = y 2
2 a c ⋅ b = 2 ( 2 x ⋅ y ) ( 2 x ⋅ z ) ( 2 y ⋅ z ) = z 2
So we could substitute x 2 , y 2 , and z 2 with a , b , and c in side length A , B , and C .
A = b a ⋅ c ⋅ 2 + c a ⋅ b ⋅ 2
B = c a ⋅ b ⋅ 2 + a b ⋅ c ⋅ 2
C = a b ⋅ c ⋅ 2 + b a ⋅ c ⋅ 2
Let's simplify Heron's formula by substitute s as A , B , and C .
a r e a = s ( s − A ) ( s − B ) ( s − C )
Where
s = 2 ( A + B + C )
So
a r e a = ( 2 ( A + B + C ) ) ( 2 ( A + B + C ) − A ) ( 2 ( A + B + C ) − B ) ( 2 ( A + B + C ) − C )
a r e a = ( 2 ( A + B + C ) ) ( 2 ( − A + B + C ) ) ( 2 ( A − B + C ) ) ( 2 ( A + B − C ) )
a r e a = ( 1 6 ( A + B + C ) ( − A + B + C ) ( A − B + C ) ( A + B − C ) )
a r e a = ( 1 6 − A 4 + 2 A 2 B 2 + 2 A 2 C 2 − B 4 + 2 B 2 C 2 − C 4 )
Then we could substitute A , B , and C as a , b , and c .
( 1 6 − ( c a ⋅ b ⋅ 2 + b a ⋅ c ⋅ 2 ) 2 + 2 ( c a ⋅ b ⋅ 2 + b a ⋅ c ⋅ 2 ) ( c a ⋅ b ⋅ 2 + a b ⋅ c ⋅ 2 ) − ( c a ⋅ b ⋅ 2 + a b ⋅ c ⋅ 2 ) 2 + 2 ( c a ⋅ b ⋅ 2 + b a ⋅ c ⋅ 2 ) ( a b ⋅ c ⋅ 2 + b a ⋅ c ⋅ 2 ) + 2 ( c a ⋅ b ⋅ 2 + a b ⋅ c ⋅ 2 ) ( a b ⋅ c ⋅ 2 + b a ⋅ c ⋅ 2 ) − ( a b ⋅ c ⋅ 2 + b a ⋅ c ⋅ 2 ) 2 )
And we simplify:
4 1 c a ⋅ b ⋅ 2 b a ⋅ c ⋅ 2 + 4 1 a b ⋅ c ⋅ 2 b a ⋅ c ⋅ 2 + 4 1 c a ⋅ b ⋅ 2 a b ⋅ c ⋅ 2
b a ⋅ c ⋅ a b ⋅ c + c a ⋅ b ( b a ⋅ c + a b ⋅ c )
a 2 + b 2 + c 2
Boom we got the answer!
Problem Loading...
Note Loading...
Set Loading...
This problem may remind you of the Pythagoras' Theorem but in 3D. Instead of the length of two legs, we have the areas of three triangular faces a = △ O X Y , b = △ O Y Z , and c = △ O X Z . Instead of finding the length of the hypotenuse, we are trying to find the area of the triangle "hypotenuse" △ X Y Z . Coincidentally, the formula is similar to the 2D Pythagoras' Theorem but with an extra variable: a 2 + b 2 + c 2 .
Let's try to prove it formally. There's a couple of methods that we can use here, but I will try working with vectors. (Another method involves finding the base and subsequently the height of △ X Y Z through repeated use of Pythagoras' Theorem.)
If we are given two sides of a triangle in vector form u , v , we can find its area using the cross product with 2 1 ∣ u × v ∣ .
Suppose that the vector from O to X is x = ⎝ ⎛ x 0 0 ⎠ ⎞ , that from O to Y is y = ⎝ ⎛ 0 y 0 ⎠ ⎞ , and that from O to Z is z = ⎝ ⎛ 0 0 z ⎠ ⎞ .
If you're wondering why we introduced new variables here, realize that the areas of a = △ O X Y , b = △ O Y Z , and c = △ O X Z can be easily expressed in terms of x , y , z . In fact, a = 2 1 x y , b = 2 1 y z , and c = 2 1 x z , respectively, which we will use later.
Now, we try to find two sides of △ X Y Z . In this example, I'm going to use X Y and X Z .
Using vector algebra, we have X Y = y − x = ⎝ ⎛ 0 − x y − 0 0 − 0 ⎠ ⎞ = ⎝ ⎛ − x y 0 ⎠ ⎞ and X Z = z − x = ⎝ ⎛ 0 − x 0 − 0 z − 0 ⎠ ⎞ = ⎝ ⎛ − x 0 z ⎠ ⎞ .
With this, we can finally find the area:
2 1 ∣ X Y × X Z ∣ = 2 1 ∣ ∣ ∣ ∣ ∣ ∣ ⎝ ⎛ − x y 0 ⎠ ⎞ × ⎝ ⎛ − x 0 z ⎠ ⎞ ∣ ∣ ∣ ∣ ∣ ∣
Computing the cross product, we have = 2 1 ∣ ∣ ∣ ∣ ∣ ∣ ⎝ ⎛ y z x z − x y ⎠ ⎞ ∣ ∣ ∣ ∣ ∣ ∣ = 2 1 ( y z ) 2 + ( x z ) 2 + ( − x y ) 2
Now, bring in the 2 1 from the outside: = ( 2 1 y z ) 2 + ( 2 1 x z ) 2 + ( 2 1 x y ) 2
Remember how we said that a = 2 1 x y , b = 2 1 y z , and c = 2 1 x z ? Substitute these in to get the final result:
a 2 + b 2 + c 2